Lutter contre la pollution lumineuse - Dany Lapostolle; Samuel Challéat (VertigO)
The degradation of darkness through the use of artificial light at night (ALAN) in and around human infrastructures is termed light pollution. This pollution is intrinsically related to urbanization and spills out from urban areas to affect rural areas and protected areas. The fight against light pollution is being organized in several countries where local communities are experimenting with environmental policies to protect darkness. The challenge bears on both the preservation of biodiversity and the energy transition. In France, a few pioneering rural areas are experimenting with mechanisms that include this dual implication. Two of them provide the case study for this article. We show how these areas turn darkness into a specific resource. We identify three specification processes. The first, obeying an anthropocentric utilitarian rationale, is part of the “economicization” of the environment in the line of shallow ecology. The second, following a rationale of ecocentric conservation, is part of the radical greening of the economy, in line with deep ecology. The third follows an integrated social-ecological system rationale enshrining the interdependence between development and planning and the preservation of biodiversity and energy savings. Specification controversies beset local areas. These areas become incubation rooms, that is, spaces for resolving these controversies that are reflected in a transition operator enabling the local area to take a fresh trajectory in terms of development and planning.